The impact of digital financial inclusion on household financial vulnerability in China: An empirical study based on CFPS - Shirui, Zhang; Mansur, Mustazar; Hidthiir, Mohammad Helmi Bin; Ahmad, Zaki; Abubakr, Ayman Abdalla Mohammed (Asian Economic and Financial Review, 2025)
Digital Financial Inclusion (DFI) has developed rapidly worldwide and is considered an important tool to alleviate Household Financial Vulnerability (FV). However, most of the existing studies are limited to short-term effects and are based on single-time cross-sectional data, lacking a dynamic analysis of the impact of digital inclusive finance before and after. Therefore, based on the CFPS data from 2018 and 2022, employing an Ordered Probit regression model and its marginal effect analysis, combined with mediating effect tests, heterogeneity analysis, and robustness tests, the following hypotheses are verified: (1) DFI significantly reduces household financial vulnerability; (2) this effect is partly realized by increasing household income and easing credit constraints; (3) low-income households and economically underdeveloped areas rely more on DFI to alleviate financial vulnerability; (4) after the epidemic, the mitigation effect of DFI on household financial vulnerability is enhanced. The results show that digital financial inclusion plays a significant role in reducing household financial vulnerability, and digital inclusive finance can also reduce household financial vulnerability by increasing household income. At the same time, the role of digital inclusive finance is more significant in economically developed regions and low-income families. Additionally, the marginal effect of digital financial inclusion is stronger in 2022 after the pandemic compared to 2018.